Modern View on the Problem of Treatment of Traumatic Soft Tissue Detachments - A. V. Nevedrov; A. P. Vlasov; K. V. Svetlov; R. I. Valieva; N. N. Zadneprovsky; P. A. Ivanov (Неотложная медицинская помощь)
The treatment of traumatic soft tissue detachments is an urgent problem for a first-level trauma hospital. This paper provides an analysis of the literature sources of the PubMed database, which are devoted to the classification, diagnosis and treatment of traumatic skin detachments. It was revealed that most of the works are publications of 1–2 clinical cases, only a few works are retrospective studies of patient groups. Currently, there is no generally accepted classification of traumatic detachment of soft tissues, due to the complexity and mosaic nature of pathoanatomical signs. According to the tactics of treatment, there is a difference in approaches for low-energy trauma (sports injury) and high-energy impact (traffic accidents, falls from a height). In the first case, the treatment methods are compression therapy, physiotherapy, and in rare cases, puncture. In the second case, puncture and drainage are the main method of treatment, and in persistent recurrent cases, chemical ablation or open surgery to excise the capsule in combination with vacuum drainage are the methods of treatment. Methods of endoscopic treatment of the walls of the detachment, ligation of the lymphatic vessels around the detachment, and the use of blockable sutures for obliteration of the detachment cavity are currently new methods of treatment, which effectiveness requires further study.